2008
DOI: 10.1002/app.28141
|View full text |Cite
|
Sign up to set email alerts
|

Influence of blending sequence on micro‐ and macrostructure of PA6/mEPDM/EPDMgMA blends reinforced with organoclay

Abstract: The structure of the PA6/mEPDM/EPDMgMA/organoclay ternary hybrids was characterized and related to its properties. The nanoblends were prepared through four different blending sequences based on one-or two-step processes: (1) The PA6/organoclay nanocomposite was prepared and then mixed with the mEPDM1 EPDMgMA compound; (2) the mEPDM1EPDMgMA1 organoclay compound was first prepared and then mixed with PA6; (3) the PA6, mEPDM, EPDMgMA, and organoclays were blended in one step; and (4) the PA6/mEPDM/EPDMgMA blend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…These results indicate that the reinforcing ability of the OMMT in this study was similar regardless of whether it was located within the main matrix phase (PLA/OMMT) or within the minor dispersed phase (PLA/PCL/OMMT). These findings are consistent with those observed in PA6/elastomer/OMMT nanocomposites, 8 where the reinforcing effect of the OMMT was also similar irrespective of its matrix-or dispersed phase-location. The good dispersion and similar intercalation level shown by the OMMT in both the binary and ternary systems of this work is also consistent with these results.…”
Section: Mechanical Propertiessupporting
confidence: 90%
See 1 more Smart Citation
“…These results indicate that the reinforcing ability of the OMMT in this study was similar regardless of whether it was located within the main matrix phase (PLA/OMMT) or within the minor dispersed phase (PLA/PCL/OMMT). These findings are consistent with those observed in PA6/elastomer/OMMT nanocomposites, 8 where the reinforcing effect of the OMMT was also similar irrespective of its matrix-or dispersed phase-location. The good dispersion and similar intercalation level shown by the OMMT in both the binary and ternary systems of this work is also consistent with these results.…”
Section: Mechanical Propertiessupporting
confidence: 90%
“…The location of the nanofillers is usually established by the chemical affinity between the different system constituents . However, under nonequilibrium processing conditions, kinetic effects, such as the blending sequence employed, must be considered as factors which may affect the location of the nanofiller in any of the separated polymer phases . The location of the fillers is of prime importance because it usually governs the final morphology of the system.…”
Section: Introductionmentioning
confidence: 99%
“…The first approach was directly adding elastomers or maleic anhydride grafted elastomers into the PA6 matrix. [9][10][11][12][13][14][15] However, the toughening with elastomer always accompanied with enormous loss in tensile properties and HDT. The second approach was to obtain some "core-shell" toughening particles by skillfully utilizing the interfacial tension in ternary blends during the melting blending process.…”
Section: Introductionmentioning
confidence: 99%
“…The additionally improved compatibilization was attributed to a more effective reaction between the maleic groups of mSEBS and the amine end groups of PA6 by substituting the interaction between the surfactant of organoclay and mSEBS. Gallego et al12 prepared organoclay‐filled PA6/mEPDM/EPDM‐g‐MA using four types of compounding sequences, and found that mixing all the components simultaneously or mixing organoclay with premixed PA6/mEPDM/EPDM‐g‐MA gave smaller average particle size than the other two compounding sequences. Zhang et al13 reported that mixing organoclay or PA6/organoclay with PA6/EPDM‐g‐MA preblends resulted in finer phase morphology than one‐step mixing or mixing PA6/organoclay with EPDM‐g‐MA in the preparation of PA6/EPDM‐g‐MA/organoclay nanocomposites, due to the avoidance of interaction between the surfactant of organoclay and EPDM‐g‐MA.…”
Section: Introductionmentioning
confidence: 99%